205 Influence of Nox NADPH Oxidases on Human Partial Induced Pluripotent Stem Cell-Derived Endothelial Cells. (3rd June 2016) - Moez, Arya; O'Neill, Karla; Margariti, Andriana; Grieve, David
Abstract : Background: Human induced pluripotent stem (iPS) cell-derived endothelial cells (ECs) hold clear potential for therapeutic angiogenesis as a novel strategy for ischaemic disease. Recently, our group has developed a novel method for direct reprogramming of partial iPS (PiPS) cells, which unlike iPS cells, are generated before pluripotency so do not form tumours. Importantly, PiPS cells may be differentiated into ECs with characteristic morphology and pro-angiogenic actions, which in vitro and in vivo studies have demonstrated are comparable to mature ECs with regard to their capability of forming vascular-like tubes and re-endothelialisation of ischaemic tissue. It is well established that oxidative stress and reactive oxygen species (ROS), which are characteristic features of ischaemic disease, are important regulators of both endothelial and stem cell biology, with recent evidence suggesting a key role for NADPH oxidases. Notably, we have previously identified a key role for the Nox4 isoform in regulating angiogenesis. The aim of the present study was therefore to investigate the specific influence of Nox NADPH oxidases on PiPS-derived ECs. Methods: Human neonatal lung fibroblasts were subjected to direct reprogramming by viral transduction with the transcription factors, OCT4, SOX2, Klf4 and c-Myc, for 4 days to generate PiPS cells, which were then seeded on mouse collagen IV in EGM-2 media for a further 6 days to induce EC differentiation. Results: PiPs cells were defined by induced expression of KDR and CD34, whilst PiPS-ECs were characterised by expression of endothelial markers, CD144 and CD31. Expression of NADPH oxidase isoforms, Nox1, Nox2 and Nox4 (as assessed by real-time RT-PCR) was progressively induced during reprogramming and EC differentiation (e.g. Nox4 mRNA: fibroblasts, 2.1 ± 0.2; PiPS, 36 ± 4; PiPS-ECs, 133 ± 29 arbitrary units; n = 3, P < 0.001), with comparable levels observed in PiPS-ECs (Nox1 mRNA, 126 ± 20; Nox2 mRNA, 82 ± 20; Nox4 mRNA, 133 ± 29 arbitrary units; n = 3, P=NS). Notably, mRNA expression of Nox4, which has been previously linked with angiogenesis, was markedly increased during hypoxia (1% oxygen) in PiPS-ECs compared with the other two isoforms (Nox1, 2.89 ± 0.26; Nox2, 1.52 ± 0.06; Nox4, 8.04 ± 0.76 arbitrary units; n = 3, P < 0.001). Conclusions: These data suggest that NADPH oxidases, particularly Nox4, may be important in mediating angiogenic function in PiPS-ECs. Future work will investigate whether genetic modification of Nox4 can influence reprogramming and differentiation of PiPS-ECs and consequently their ability to promote angiogenesis in response to experimental ischemia.